When more is not better: Complementarities, costs and contingencies in stakeholder management - Garcia-Castro, Roberto; Francoeur, Claude (Strategic management journal, 2016)
Instrumental stakeholder theory has largely emphasized the positive effects of investing in stakeholder cooperative relationships in an additive, linear fashion in the sense that the more investments the better. Yet investing in stakeholders can be very costly and the effects of these investments in firm performance are subject to complex internal complementarities and external contingencies. In this article we rely on set-theoretic methods and a large international dataset of 1,060 multinational companies to explore theoretically and empirically some of the complementarities, costs and contingencies likely to arise in stakeholder management.